2006
DOI: 10.1002/nau.20289
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic bladder treatment by doubling the recommended antimuscarinic dosage

Abstract: The increased dosage of Tolterodine or Trospium is an effective treatment in patients with neurogenic bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 11 publications
1
50
0
2
Order By: Relevance
“…The first assumption is the additive effect of regular dosages of two antimuscarinics. 11,12 However, it seems unreasonable to simply connect our results with a dose-dependent effect because our results demonstrated the enhanced efficacy of combined medication in patients who did not respond to double-dosing monotherapy. Second, different receptor selectivity of two antimuscarinics might be considered.…”
Section: Drug Combinations Nmentioning
confidence: 82%
“…The first assumption is the additive effect of regular dosages of two antimuscarinics. 11,12 However, it seems unreasonable to simply connect our results with a dose-dependent effect because our results demonstrated the enhanced efficacy of combined medication in patients who did not respond to double-dosing monotherapy. Second, different receptor selectivity of two antimuscarinics might be considered.…”
Section: Drug Combinations Nmentioning
confidence: 82%
“…This can be explained by the fact that neurogenic bladders are often more refractory to medical therapies, as pointed out by Horstmann and colleagues. 22 A 94% success rate in the non-neurogenic group is therefore reassuring since other treatments, such as intravesical oxybutynin, sacral neuromodulation or botulinum toxin (with their inherent 5% to 11% risk of clean intermittent catheterization), 23,24 would be deferred. For non-responders or children responding only partially to therapy, initial urodynamics were less favourable (stronger uninhibited detrusor contractions and smaller bladder capacity).…”
Section: Discussionmentioning
confidence: 99%
“…22 Doubling the recommended AM dosage in patients nonresponsive to recommended doses improved urodynamic parameters significantly. 26 Moreover, the same authors showed that 85% of patients nonresponsive to dosage-escalated monotherapy could be treated successfully by combined high-dose AM. 27 Various studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six studies investigated, whether flexible dosing improved therapeutic response (Table 1d), two with oxybutynin ER, 22,23 one with trospium chloride IR, 24 one with solifenacin, 25 one compared oxybutynin IR with tolterodine IR, 16 another tolterodine ER with trospium chloride IR. 26 Two studies combined high-dose AM in patients nonresponsive to dosage-escalated monotherapy. 27,28 Various studies.…”
Section: Study Characteristicsmentioning
confidence: 99%